T1 Bacteria can trigger airway sensory nerves via the activation of tlr2. (15th November 2017) - Wortley, MA; Dubuis, ED; Bonvini, SJ; Birrell, MA; Belvisi, MG
Abstract : Introduction: Excessive coughing is a key symptom of lower respiratory tract infections (LRTI's) especially when associated with exacerbations of respiratory diseases like asthma and COPD. 1, 2 As airway sensory nerve activation is required to trigger the cough response, we hypothesised that respiratory related bacteria could fire these nerves. Methods: In vitro tissue and neuron assay systems were employed, in conjunction with in vivo electrophysiology and a guinea pig cough model to investigate this hypothesis. Results: We show that a bacterial mimetic, LPS can activate guinea pig sensory nerve fibres in vivo . Furthermore, LPS, as well as heat-killed bacteria ( Haemophilus Influenzae and Streptococcus Pneumoniae ), activated isolated sensory nerve tissue (vagus) from guinea pigs (LPS 0.11±0.04 mV; HI 0.14±0.02 mV; SP 0.16±0.05 mV, n=3) with similar Results in tissue obtained from human donor lungs and c57bl/6 mice. An investigation into the Toll-like receptor (TLR) involved revealed that it was TLR2, and not TLR4, with a TLR2 agonist (lipotechoic acid, LTA) causing activation of isolated vagus (0.14±0.02 MTV), whereas a TLR4 agonist (ultra-pure LPS) did not (0.00±0.00 mV). Furthermore LPS activated wild-type mouse vagus nerve (0.12±0.01 mV) whereas it had little effect in TLR2-/- mouse vagus nerve (0.02±0.00 mV). Indeed, using single cell RT-PCR, we found guinea pig airway-terminating neurons expressed TLR2 (3/69), but not TLR4 receptors (0/69). Further investigation showed that the TLR2 response at least partially required TRPA1 ion channels, with 55.25%±3.51% inhibition of LPS responses by the TRPA1 inhibitor J130. Conclusion: We have shown that bacteria can activate the sensory nerves associated with the cough response. We propose that this could be an endogenous defensive mechanism designed to expel bacterial infection, and/or could be a method harnessed by some infective agents to spread from carrier to new host. Furthermore, increased understanding of the mechanisms involved may lead to an insight into ways to modulate the excessive coughing, which plagues respiratory patients during exacerbation episodes. References: Everard. Paediatr Respir Rev 2012;13:139–143. Bourbeau. Chest 2015;147:894–942.